Changes in children's meal orders following healthy menu modifications at a regional US restaurant chain. (May 2015) - Anzman‐Frasca, Stephanie; Mueller, Megan P.; Sliwa, Sarah; Dolan, Peter R.; Harelick, Linda; Roberts, Susan B.; Washburn, Kyle; Economos, Christina D.
<x xml:space="preserve">Abstract</x> Objective To examine changes in children's meal orders, price, and revenue following the implementation of a healthier children's menu in a full‐service restaurant chain. Methods In April 2012, the healthier menu was implemented, featuring more meals meeting nutrition standards, healthy side dishes by default, and removal of French fries and soda (which could be substituted). Orders (n = 352, 192) were analyzed before (September 2011 to March 2012; PRE) and after (September 2012 to March 2013; POST) implementation. Results Children's meal prices increased by $0.79 for breakfasts and $0.19 for non‐breakfast meals from PRE to POST. Revenue continued to increase post‐implementation. Orders of healthy meals, strawberry and vegetable sides, milk, and juice increased, and orders of French fries and soda decreased (P < 0.0001). Orders at POST were more likely to include healthy sides (P < 0.0001) and substitutions (P < 0.0001) and less likely to include a la carte sides (P < 0.0001) and desserts (P < 0.01), versus PRE. Total calories ordered by children accepting all defaults decreased (684.2 vs. 621.2; P < 0.0001) and did not change for those not accepting defaults (935.0 vs. 942.9; P = 0.57). Conclusions Healthy children's menu modifications were accompanied by healthier ordering patterns, without removing choice or reducing revenue, suggesting that they can improve child nutrition while restaurants remain competitive.